A prospective study of drug utilization pattern in cardiac intensive care unit at a tertiary care teaching hospital - Nagabushan, H.; Roopadevi, H. S.; Prakash, G. M.; Pankaja, R. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Cardiovascular diseases remain the most common cause of sudden death. Appropriate drug therapy in cardiac intensive care unit (CICU) is crucial in managing cardiovascular emergencies and to decrease morbidity and mortality. The present study was conducted to observe the emergency cardiac diseases which are most frequently being treated and to study the prescribing prevalence among inpatients in CICU. Methods: A prospective, observational study was carried out among 102 patients admitted in CICU at a tertiary care teaching hospital, Karnataka, for a period of 3 months. Demographic data, clinical history, and complete drug therapy received during their stay in CICU was noted. Results: In our study, males (64.7%) had a higher incidence of cardiovascular emergencies than females (35.3%). Hypertension (32.4%) and Type 2 diabetes mellitus (28.4%) were the frequently associated co-morbid conditions. Antiplatelet drugs 80 (78.4%) was most commonly prescribed, followed by hypolipidemic drugs 75 (73.5%) and anticoagulants 65 (63.7%). The mean duration of stay in the hospital was 4.79±1.9 days. The average number of drugs per prescription was 7.8±2.2. Percentage of drugs prescribed by generic names was 52.9%. The percentage of drugs prescribed from essential drug list was 75.1%. Conclusions: Antiplatelet drugs were the most frequently prescribed drug group. Mean number of drugs per prescription were high. The prescribing pattern could be improved by reducing the number of drugs per prescription and by prescribing generic drugs to reduce the economic burden of the patients.